The Inhibition of Platelet Aggregation by an Aorta Intima Extract - Heyns, A. du P; van den Berg, D. J; Potgieter, G. M; Retief, F. P (Thrombosis and Haemostasis, 1974)
The platelet aggregating activity of extracts of different layers of the arterial wall was compared to that of Achilles tendon. Arterial media and tendon extracts, adjusted to equivalent protein content as an index of concentration, aggregated platelets to the same extent but an arterial intima extract did not aggregate platelets. Platelet aggregation induced by collagen could be inhibited by mixing with intima extract, but only to a maximum of about 80%. Pre-mixing adenosine diphosphate (ADP) with intima extracts diminished the platelet aggregation activity of the ADP. Depending on the relationship between ADP and intima extract concentrations aggregating activity could either be completely inhibited or inhibition abolished. Incubation of ADP with intima extract and subsequent separation of degradation products by paper chromatography, demonstrated a time-dependent breakdown of ADP with AMP, adenosine, inosine and hypoxanthine as metabolic products; ADP removal was complete. Collagen, thrombin and adrenaline aggregate platelets mainly by endogenous ADP of the release reaction. Results of experiments comparing inhibition of aggregation caused by premixing aggregating agent with intima extract, before exposure to platelets, and the sequential addition of first the intima extract and then aggregating agent to platelets, suggest that the inhibitory effect of intima extract results from ADP breakdown. It is suggested that this ADP degradation by intima extract may play a protective role in vivo by limiting the size of platelet aggregates forming at the site of minimal “wear and tear” vascular trauma.